Poverty, education and health insurance coverage among women of reproductive ages in the Democratic Republic of the Congo: a cross-sectional and multilevel analysis. Issue 12 (13th December 2022) - Tsala Dimbuene, Zacharie; Muanza Nzuzi, Raphaël; Nzita Kikhela, Paul-Denis
Abstract : Objective: To investigate inequalities of health insurance coverage (outcome) at subnational level, and the effects of education and poverty on the outcome. Design: Secondary analysis of Demographic and Health Surveys. The outcome variable was health insurance ownership. Setting: The Democratic Republic of the Congo. Subjects: Women aged 15–49 years (n=18 827). Results: Findings indicated significant spatial variations of the health insurance ownership which ranged from 1.2% in Bandundu and Kasaï Oriental to 15.5% in Kinshasa the Capital City. Furthermore, findings showed that an additional year of women education increased by 10% the chance of health insurance ownership (adjusted OR, AOR 1.098; 95% CI 1.065 to 1.132). Finally, living in better-off households increased by 150% the chance of owing a health insurance (AOR 2.501; 95% CI 1.620 to 3.860) compared with women living in poor households. Conclusions: Given the low levels of health insurance coverage, the Democratic Republic of the Congo will not reach the Sustainable Development Goal 3, aimed at improving maternal and child health unless a serious programmatic health shift is undertaken in the country to tackle inequalities among poor and uneducated women via universal health coverage.